The Microbiological Hazards of Enterobacter spp. Contamination in Street Food in Developing Countries: A Literature Review - Pareakan, Jefyne Mali’; Amarantini, Charis; Budiarso, Tri Yahya (Journal of Health and Nutrition Research, 2025)
Street food is widely consumed by people in developing countries and often poses health risks due to bacterial contamination. The consumption of contaminated food has been linked to more than 200 types of diseases, resulting in 600 million cases and 420,000 deaths each year. One commonly found bacterium is Enterobacter, which can be pathogenic and exhibit resistance to various antibiotics. This review aims to assess the dangers of Enterobacter contamination in street food, including the level and source of contamination, pathogenicity, and management strategies. The review followed PRISMA 2020 guidelines, with literature searches performed in scientific databases such as PubMed and Google Scholar using Boolean operators and relevant keywords. Articles were selected based on specific inclusion criteria, analyzed, and grouped for ease of interpretation. The results showed that Enterobacter contamination is prevalent in developing countries such as Nigeria, Ghana, Ethiopia, Pakistan, India, and Indonesia. Nigeria recorded the highest prevalence, with E. aerogenes reaching 100% in ready-to-eat rice. The primary source of contamination is raw materials, particularly wheat flour, which contains E. sakazakii with a prevalence of 100%. Enterobacter can cause various serious infections, including urinary tract infections, meningitis, pneumonia, and septicemia. Efforts to reduce Enterobacter contamination in street food should include the implementation of hygiene and sanitation practices, the use of safe raw materials, proper processing and storage methods, education for vendors, and routine food safety supervision. These findings are crucial for supporting public health interventions and developing effective food safety policies.